Analisis Usability Aplikasi Mobile Layanan Paspor Online Menggunakan Metode Usability Testing (Studi Kasus : Kantor Imigrasi Kelas I Malang) - Apriani Ingin Marito Tampubolon; Retno Indah Rokhmawati; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Layanan Paspor Online is a mobile application for online passport queue registration developed by Directorate General of Immigration Indonesia which has been implemented at Malang Class I Immigration Office. But in its application there are some problems such as the colors that are too flashy, the registration process is complicated, less attractive design, and less user friendly where people who lack of knowledge about technology find it difficult to use this application. Based on these problems, it is necessary to analyze and improve the user interface using usability testing method. The usability aspect used in this method are learnability, efficiency, error, and satisfaction. Respondents who participated in this study were 5 people for usability testing and 20 people for system usability scale questionnaire. The result of the learnability aspect measured using success rate metric increased from before the improvement by 90% to 98,6% after the improvement. The efficiency aspect measured using time based efficiency metric increased from before the improvement by 0,2 goals/sec to 0,3 goals/sec after the improvement. The error aspect measured using defective rate metric decreased from 8,90% to 1.1%. The satisfaction aspect measured using System Usability Scale (SUS) questionnaire increased from before the improvement by 66 to 77 after the improvement. From these result, the improvement given to Layanan Paspor Online application can fix the problem found.